(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2019)
Five stable isomers of antiviral ribavirin agent were theoretically determined in gas and aqueous solution by using the hybrid B3LYP/6-31G* method. Here, the solvent effects were studied with the self consistent reaction field (SCRF) methodology employing the polarized continuum (PCM) and the universal solvation model (SM). Structural, electronic and topological properties were reported for all isomers while the vibrational analyses were performed only for those two polymorphic structures experimentally observed in the solid phase by X-ray diffraction. Calculations have evidenced that C2 correspond to the polymorphic V1 structure while C5 to the polymorphic V2 structure. The high dipole moment values predicted for C2 and C5 in both media could probably explain their presences in the solid. Experimental available IR and Raman spectra of ribavirin in the solid state and normal internal coordinates were employed together with the scaled quantum mechanical force field (SQMFF) approach to perform the complete vibrational assignments in both media. Here, the 81 vibration modes expected for C2 and C5 in both media were completely assigned. The frontier orbitals studies reveal that C5 is the less reactive in both media. Here, the gap value observed for C5 is in agreement with the value recently reported for ribavirin by using B3LYP/6-311++G** calculations.